(untitled) (Research, Society and Development, 2022)
The umbilical cable is today an important technology used to control equipment on the seabed in the production of offshore oil in deep and ultra-deep waters. The umbilical is composed of several components, including steel tube for transporting fluids for hydraulic control of equipment in the bed. Such tubes are susceptible to fatigue during their life in umbilical operation. Fatigue strength is influenced by the accumulated plastic strain (APS) undergone by the tubes during the entire manufacturing process until installation/storage on spools. This present study investigated whether the way in which the APS is applied influences the fatigue strength of the tubes. Fatigue test specimens were machined from super duplex umbilical tube, which received 5% of APS by cyclic bending in two different ways: repeated bending and alternating bending. Microstructural and microhardness analyzes were performed on the specimens after fatigue fracture. No significant difference neither in microstructure, nor on the microhardness of the two groups of specimens was found after fatigue fracture. However, the group subjected to alternating plastic strain experienced lower fatigue strength. Therefore, the way in wich the tubes are deformed during manufacture and storage influences their fatigue performance.